Effect of Groundnut Shell Ash on Laterite Soils Stabilized with Lime for Civil Structures - Adetayo, Oluwaseun; O. Amu, Olugbenga; Faluyi, Feyidamilola; Akinyele, Emmanuel (International Journal of Integrated Engineering, 2021)
This research considered the viability of groundnut shell ash (GSA) on lime stabilized lateritic soil for roadway structural works. Three samples of lateritic soil named samples A, B and C were gathered from Idita-Mokuro, NTA-Mokuro and ETF burrow pits individually, in Ile-Ife, Osun State, Nigeria. Preliminary tests were completed on the samples in their natural states and when stabilized with optimum lime. Engineering tests were performed while varying rates of GSA were added to the soil samples at optimum lime. The Atterberg limits tests showed a significant reduction in plasticity index for samples A and C when stabilized with lime. Compaction test showed a decrease in the maximum dry density from 1685kg/m3 to 1590kg/m3 for sample A, 1599kg/m3 to 1512kg/m3 for sample B and 1396kg/m3 to 1270kg/m3 for sample C on stabilizing with lime, introduction of GSA to stabilized lime-soil diminishes the maximum dry density for all the soil samples with sample A reduced to 1435kg/m3, 1385kg/m3, and 1350kg/m3 at 2, 4 and 6% GSA contents respectively. Addition of GSA contents improved the engineering properties of lime stabilized soils as the unsoaked CBR esteems expanded for all soil samples. At optimum lime dosage, addition of 2%  GSA content expanded the triaxial shear strength from 60.43kN/m2 to 188.36kN/m2 for sample A, and at 4% GSA content, both soil samples B and C increased from 19.19kN/m2 to 201.48kN/m2 and 30.62kN/m2 to 111.65kN/m2 respectively. Conclusively, groundnut shell ash improved the toughness and strength of lime stabilized lateritic soil for highway structural works. is compulsory. First sentence describes the nature or the background information on the field of study. Subsequent sentences provide the problem statement or objectives and scope of the research. Next sentences explain the methods and materials used in the work. Main results and important findings are then highlighted. Finally, a summary of conclusions is put forth. Length of abstract can be proportional to the length of the article